Application of Semantic Web Technologies to Verification of Business Requirements - Shuvalova, Anastasia; Svátek, Vojtěch, 1967 prosinec 1.-; Jirkovský, Václav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2021)
Within the current master thesis the author intended to elaborate on the partial automation of the Change Management process for the large-scaled enterprise. The main aim was to design the solution that allows employees without programming skills to adjust the automated validation of the Requests for Change for the current needs. Another goal was to leverage the potential of Semantic Web technologies for modeling (with RDF and OWL) and verifying (with SWRL) the requirements. The required ontology describing the problematic area was created. The validation mechanism based on the SWRL rules than was proposed. These rules are later made available for modifications for the stakeholders. The solution integrates the OWL ontology and the set of designed SWRL rules and is represented in the form of the REST API written in Python language. The API performs the validation of the incoming data regarding the newly created requests and returns the obtained results to the end users.
Vedoucí práce: Vojtěch Svátek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: znalostní a webové technologie [obor dipl. práce]; diplomové práce; master's theses